Neural Correlates of Interval Timing Deficits in Schizophrenia - Snowden, Ariel W.; Buhusi, Catalin V. (Frontiers in Human Neuroscience, 2019)
Previous research has shown that schizophrenia patients exhibit impairments in interval timing. The cause of timing impairments in schizophrenia remains unknown but may be explained by a dysfunction in the fronto-striatal circuits. Although the current literature includes extensive behavioral data on timing impairments, there is limited focus on the neural correlates of timing in schizophrenia. The neuroimaging literature included in the current review reports hypoactivation in the dorsal-lateral prefrontal cortex, supplementary motor area and the basal ganglia. Timing deficits and deficits in attention and working memory in schizophrenia are likely due to a dysfunction of dopamine and GABA neurotransmission in the cortico-striatal-thalamo-cortical circuits, which are highly implicated in executive functioning and motor preparation.